Aerial Landmine Detection - Gaur, Pushkar; Choudhary, Tanishq (International Journal of Engineering and Technology, 2018)
This paper aims at designing a quad copter which not only capable of detecting landmines but simultaneously has innumerable other applications, putting the feudal way of losing life at rest. The quad copter uses four brushless motors connected to the flight control microcontroller board through electronic speed control (ESC) module, which will provide the necessary thrust and greater maneuverability. The whole set up is remotely controlled by the help of NRF module and powered by 2200mAh 3s lipo battery. The quad copter consists of a mine detector sensor, wireless camera and detonation system all of which will in turn be connected to the Raspberry-pi for wireless control and processing. The camera provides the real time image to the raspberry pi which will do digital image processing on it and give out digitally enhanced images for edge detection making it easier for the user to detect the mines. Further it will also help in detecting surface mines present in water thus imparting twin benefit. In the detonation system, servo motors are used to open the gate of the box containing detonation material which fall on the mine to neutralize them.Â Â